The Entrepreneurial University: Conceptualisation, Models and Challenges for Operationalisation of the Concept - Badzińska, Ewa (Contemporary organisation and management. Challenges and trends, 2020)
The nature of the study is descriptive, and the methods used in this objective are a critical review of the subject literature, defining, comparing, analysis, reflection, and inference. The paper concludes with recommendations and directions for an in-depth empirical research. In order to obtain a deeper insight into the research problem the future investigation will focus on the identification of critical factors related to the transformation process into an Entrepreneurial University using multiple case studies. Although the concept has received considerable attention over the last years, further comparative studies of the practical aspects of its implementation and impact are expected to create a coherent and widely recognized conceptual and measurement apparatus.